Mulheres mastectomizadas: o que muda na dinâmica conjugal? - Vieira, Teresa Cristina da Costa (2016)
The diagnosis of breast cancer triggers changes in functioning not only of women so diagnosed, but also in your entire family, affecting even the emotional relationships and marriage. Women undergoing mastectomy may have difficulties during the return to professional activities, the social and family gatherings, as also within the sexual relationship. There is a great impact on self-esteem. The quality of life is affected and their evaluation is important for the detection of aspects that may interfere with the well-being of these women. The proposed study aimed to analyze the perception on the communication and emotions present in conjugality by women mastectomizadas as well as on the quality of life after surgery. The research of quantitative nature studied 50 mastectomizadas women, aged 30 to 55 years, served in the infirmary of a referral hospital for breast cancer, in the city of Recife. Were used as data collection instruments the Generic questionnaire of quality of life of the European Organization for Research and Treatment of Cancer Quality of Life (EORTC) QLQ-C30 version 3.0; the questionnaire to assess marital dynamics, and the Quality of life questionnaire Supplementary Questionnaire QLQ-BR23 Breast Cancer Module version 1.0. For statistical analysis, we used the software SPSS 13.0 for Windows and Excel 2010. The results were initially assessed through a descriptive analysis, based on composition of frequency tables or graphics, in addition to the calculation of some descriptive measures (average, standard deviation, minimum and maximum values of the series). To evaluate statistical significance for the assessments were used the 95% confidence intervals and the value of 0.05 for the probability associated with the tests (p value). To verify the existence of association between categorical variables were used: Chi-square and Fisher's exact test and, comparison of the groups, the Mann-Whitney Test (not Normal). The results point to the companionship between the spouses, and there is constant dialogue of the couple; most of the women were sexually active and replied that sexual activity is satisfactory. It was also observed the presence of impairment of self-image in most women and pain interfering with quality of life. On those results, it is considered relevant to encourage prevention and early diagnosis of disease; provide a follow up of a multidisciplinary team of health, to accommodate those couples, in order to encourage a better fight disease.